Clinical Decision Making in the ICU: Dysphagia Screening, Assessment, and Treatment - Brodsky, Martin B.; Mayfield, Emily B.; Gross, Roxann Diez (Seminars in Speech and Language, 2019)
Clinicians often perceive the intensive care unit as among the most intimidating environments in patient care. With the proper training, acquisition of skill, and approach to clinical care, feelings of intimidation may be overcome with the great rewards this level of care has to offer. This review—spanning the ages of birth to senescence and covering oral/nasal endotracheal intubation and tracheostomy—presents a clinically relevant, directly applicable review of screening, assessment, and treatment of dysphagia in the patients who are critically ill for clinical speech–language pathologists and identifies gaps in the clinical peer-reviewed literature for researchers.
Keywords: critical care; intensive care unit; infant; child; adult; intubation; tracheostomy; noninvasive ventilation; screening; assessment